DETERMINANTS OF PERINATAL DEPRESSION IN LICIN BANYUWANGI 2019 - Putra, Achmad Januar Er; Nurrobi, R. M. Yusuf Aji Samudera; Prasetyo, Danang Mukarrom; Akbar, Muhammad Vildan; Oktaviana, Novita; Fatimah, Aliya; Hikmahwati, Wandya; Fibularis, Alma Pustika Kartikananda Retina; Zahro, Fatimah Az; Azwan, Zahwa Afdhilani; Karimah, Azimatul; Dewi, Nira Ista (Journal of Community Medicine and Public Health Research, 2020)
Perinatal depression is a mood disorder that occurs in pregnant and postpartum women. To determine the magnitude of the risk of perinatal depression, this study uses the Edinburgh Postnatal Depression Scale (EPDS) screening tool. This study uses primary data in the form of a questionnaire to collect data on screening for depression in pregnant women and postpartum during the last 12 months. This research is an observational descriptive study with cross sectional research design. Sampling was done by cluster random sampling in Segobang Village, Jelun Village, and Banjar Village in Licin District, Banyuwangi Regency. The number of samples obtained was 31 samples. In the EPDS screening results of the pregnant women group, the results showed a very high risk of 18,75%. Whereas in the postpartum maternal group, the results showed a high risk of 6,67%, and a very high risk of 6,67%. Based on the results of the correlation test with Spearman's rho correlation, it can be concluded that there was a significant corellation between maternal age of postpartum with the risk of perinatal depression (α = 0,03).